Optical Coherence Tomography-Guided Early Versus Late Switching to Dexamethasone Implants in Macular Edema Related to Central Retinal Vein Occlusion: Real-World Evidence - Yozgat, Zübeyir (MDPI AG, 2025)
Background/Objectives: This study evaluated the outcomes of early versus late switching from intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapy to dexamethasone (DEX) implants in patients with macular edema secondary to central retinal vein occlusion (CRVO). The critical role of optical coherence tomography (OCT) in guiding therapeutic decisions and monitoring treatment responses is emphasized. Methods: In this real-world, retrospective study, 61 treatment-naïve CRVO patients were divided into two groups: Group 1 (early switch after three anti-VEGF injections) and Group 2 (late switch after six months of anti-VEGF therapy). High-resolution OCT was employed at all follow-ups to evaluate anatomical outcomes, specifically changes in central macular subfield thickness (CMST), while best-corrected visual acuity (BCVA) was assessed using standardized ETDRS charts. Results: Both groups demonstrated significant improvements in BCVA and reductions in CMST over 52 weeks. Group 1 exhibited slightly greater gains in BCVA (+20.3 ETDRS letters) and a greater CMST reduction (−201.5 µm) compared to Group 2 (+18.5 ETDRS letters, −184.4 µm), although the differences were not statistically significant. The OCT findings enabled precise monitoring and individualized treatment adjustments, reducing the treatment burden in the early-switch group with fewer anti-VEGF injections. Conclusions: Early switching to DEX implants, guided by OCT findings, may optimize therapeutic outcomes and reduce the treatment burden, particularly in real-world settings with limited resources or adherence challenges. These findings highlight the importance of incorporating advanced imaging techniques into routine practice, and underscore the need for further research on OCT-guided therapeutic transitions in macular edema management.
Keywords: Medicine (General); macular edema; optical coherence tomography; R5-920; central retinal vein occlusion; anti-VEGF therapy; dexamethasone implant; Article; real-world study